2005
DOI: 10.1104/pp.105.072579
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-Specific Induction of the Anthocyanin Biosynthetic Pathway in Arabidopsis

Abstract: Sugars act as signaling molecules, whose signal transduction pathways may lead to the activation or inactivation of gene expression. Whole-genome transcript profiling reveals that the flavonoid and anthocyanin biosynthetic pathways are strongly up-regulated following sucrose (Suc) treatment. Besides mRNA accumulation, Suc affects both flavonoid and anthocyanin contents. We investigated the effects of sugars (Suc, glucose, and fructose) on genes coding for flavonoid and anthocyanin biosynthetic enzymes in Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
620
5
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(685 citation statements)
references
References 54 publications
30
620
5
4
Order By: Relevance
“…Our results suggest that the selective degradation of BBX22 might fine-tune the expression of ELIP2 for optimal chlorophyll accumulation. BBX22 also up-regulates genes involved in flavonoid and anthocyanin biosynthesis pathways, including CHS, CHI, F3H, and 4CL3 (Li et al, 1993;Shirley et al, 1995;Ehlting et al, 1999;Raes et al, 2003;Solfanelli et al, 2006;Poustka et al, 2007;Owens et al, 2008;Buer and Djordjevic, 2009). This observation explains the excess accumulation of anthocyanin in etiolated cop1BBX22-GFPox plants (Fig.…”
Section: Bbx22 Influences Genes On Light Signaling and Hormone Responsesmentioning
confidence: 99%
“…Our results suggest that the selective degradation of BBX22 might fine-tune the expression of ELIP2 for optimal chlorophyll accumulation. BBX22 also up-regulates genes involved in flavonoid and anthocyanin biosynthesis pathways, including CHS, CHI, F3H, and 4CL3 (Li et al, 1993;Shirley et al, 1995;Ehlting et al, 1999;Raes et al, 2003;Solfanelli et al, 2006;Poustka et al, 2007;Owens et al, 2008;Buer and Djordjevic, 2009). This observation explains the excess accumulation of anthocyanin in etiolated cop1BBX22-GFPox plants (Fig.…”
Section: Bbx22 Influences Genes On Light Signaling and Hormone Responsesmentioning
confidence: 99%
“…Exogenous sucrose as an environmental factor greatly impacted plant gene expression and concentrations of cellular metabolites (Solfanelli C, 2006;Hummel M, 2009). In this study, expression profiles of genes involved in energy metabolism in Brassica napus were analyzed ( Figure 5).…”
Section: Exogenous Sucrose Regulates Expression Of the Key Genes Invomentioning
confidence: 99%
“…For example, MYB11, MYB12, MYB111, MYB75/ PAP1, and AtMYBD work as positive regulators whereas MYB-LIKE 2 (MYBL2) functions as a negative regulator. 17,19,[27][28][29][30] Among them, MYB75/PAP1 is a master regulator of the anthocyanin biosynthesis pathway; 19,31 however, direct evidence reflecting whether or not PAP1 can act on the circadian regulation of this biosynthesis pathway is still lacking. 32 Currently, a study has revealed that 2 circadian components NIGHT LIGHT-INDUCIBLE AND CLOCK-REGULATED (LNK) and RVE8 collaborate to control the anthocyanin metabolic pathway.…”
mentioning
confidence: 99%